Pencapaian Fase Embriosomatik Manggis (Garcinia mangostana L.) dengan Penambahan Thidiazuron dalam Medium Setengah MS Cair - Rineksane, Innaka Ageng (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2016)
One of the problems related to the establishment of mangosteen plantation is to obtain seedlings throughout the year, which can be solved by micropropagation.   The propagation of Mangosteen was done through somatic embryogenesis. The objective of this study was to determine the effect of Thidiazuron concentration in ½ MS medium to achieve somatic embryo stages of mangosteen seed. The study consisted of two experiments. Experiment 1: The embryogenic callus c.a.1 g derived from MS solid medium containing of Thidiazuron (0,1; 0,5; dan 1 mg/l) and 2,4-Dichlorophenoxy acetic acid (4,6,8 dan 10 mg/l) was subcultured into ½ MS0 liquid medium. 2). The embryogenic callus from the previous medium were subcultured into ½ MS liquid medium containing Thidiazuron (0, 1, 2, 4 dan 8 mg/L) and Casein hydrolysate 500 mg/L. The results showed that cell suspension were developed after mangosteen embryogenic callus subcultured into ½ MS0 liquid medium.  Somatic embryo stages such as globular, heart and torpedo were formed after the calli derived from the previous ½ MS solid medium containing 10 mg/L 2,4-D and 1 mg/L Thidiazuron were subcultured into ½ MS0 liquid medium in 8 weeks.  Cell suspension in ½ MS liquid medium with or without the addition of  Thidiazuron and Casein hydrolysate has induced the formation of embryo somatic stages such as globular, heart and torpedo after 6 months of incubation.